2019
DOI: 10.1038/s41598-019-46363-w
|View full text |Cite
|
Sign up to set email alerts
|

Bio-enzymes for inhibition and elimination of Escherichia coli O157:H7 biofilm and their synergistic effect with sodium hypochlorite

Abstract: Escherichia coli O157:H7 is one of the most important pathogens worldwide. In this study, three different kinds of enzymes, DNase I, proteinase K and cellulase were evaluated for inhibitory or degrading activity against E. coli O157:H7 biofilm by targeting extracellular DNA, proteins, and cellulose, respectively. The cell number of biofilms formed under proteinase K resulted in a 2.43 log CFU/cm 2 reduction with an additional synergistic 3.72 log CFU/cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 77 publications
(80 reference statements)
7
31
0
Order By: Relevance
“…However, DNase I and proteinase K had little effect on the biofilm matrix in the conditions used. In a study by Lim et al [66] Escherichia coli biofilms were treated with DNase I, proteinase K and sodium hypochlorite. When enzymes were added to the preformed biofilms on a stainless steel substrate, none of the DNase I, proteinase K, or NaClO treatment alone significantly reduced the number of viable cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, DNase I and proteinase K had little effect on the biofilm matrix in the conditions used. In a study by Lim et al [66] Escherichia coli biofilms were treated with DNase I, proteinase K and sodium hypochlorite. When enzymes were added to the preformed biofilms on a stainless steel substrate, none of the DNase I, proteinase K, or NaClO treatment alone significantly reduced the number of viable cells.…”
Section: Discussionmentioning
confidence: 99%
“…When enzymes were added to the preformed biofilms on a stainless steel substrate, none of the DNase I, proteinase K, or NaClO treatment alone significantly reduced the number of viable cells. However, the combined treatment using proteinase K followed by NaClO, showed a notable reduction of viable cells [66]. The role of eDNA and exoproteins on biofilm formation were investigated by George and Halami [67] by treating mature Lactobacillus plantarum biofilms with DNase I and proteinase K. While untreated biofilms were observed to possess significantly dense population of both live and dead cells, a considerable decrease in the cell density was evident in DNase I-treated and proteinase K-treated biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…(2) chemical [56][57][58]; (3) physical [59,60]; (4) physicochemical [61][62][63]; (5) physical in combination with natural [64], and (6) natural in combination with chemical [65]. A summary of the bacterial biofilm inhibition/control methods described in the past two years is shown in Figure 1.…”
Section: Biofilm Control Methodsmentioning
confidence: 99%
“…In order not to exclude search results that could be significant for the investigation, a general search term (keyword) "biofilm" was used. According to the scientific articles found in the PubMed database regarding biofilm inhibition and control, all methods, based on their nature, can be divided into six groups: (1) natural (biological) [53][54][55]; (2) chemical [56][57][58]; (3) physical [59,60]; (4) physicochemical [61][62][63]; (5) physical in combination with natural [64], and (6) natural in combination with chemical [65]. A summary of the bacterial biofilm inhibition/control methods described in the past two years is shown in Figure 1.…”
Section: Biofilm Control Methodsmentioning
confidence: 99%
“…Exopolysaccharides are secreted during E. coli O157:H7 biofilm development, and some of them include cellulose, colanic acid, and the adhesin poly-β-1,6-N-acetyl-glucosamine, and these polymers are involved in the maintenance of biofilm structure and cellular protection against disinfectants [4]. It has been reported that cellulose is the major EPS component of E. coli biofilms, and it is essential for its structure and strength, creating cell-cell and cell-surface interactions, retaining water, and avoiding the effect of disinfectants [5]. Previously it was demonstrated that degradation of the EPS matrix of E. coli O157:H7 biofilms (mainly composed by glucans) increased their susceptibility to disinfectants.…”
Section: Introductionmentioning
confidence: 99%